The prevalence and risk factors for mental distress among Syrian refugees in Germany: a register-based follow-up study - Borho, Andrea; Viazminsky, Andre; Morawa, Eva; Schmitt, Gregor Martin; Georgiadou, Ekaterini; Erim, Yesim (BMC Psychiatry, 2020)
Background: Mental disorders among refugees as well as their risk factors are already well documented in cross-sectional reports. However, longitudinal follow-up designs are widely lacking. Therefore, the aim of this study was to examine the change of the prevalence of mental disorders among Syrian refugees with German residence permission, taking into account their increasing length of stay in Germany, and to uncover the change in their relationship to pre- and post-migration risk factors. Methods: This study formed part of a register-based follow-up study with two measurement points in Erlangen (Germany). At the first time of recruitment in 2017, 200 of the 518 Syrian refugees with residence permission living in Erlangen took part. During the second survey timeframe 1.5 years later, in 2019, 108 of the former 200 Syrian refugees participated again and formed the total sample for this follow-up study. The survey instruments included demographics, migration-related variables and symptoms of post-traumatic stress (Essen Trauma Inventory, ETI), depression (Patient Health Questionnaire - PHQ-9) and generalized anxiety disorder (GAD-7). Results: At the time of the first survey, 26.9% of the participants exceeded the cut-off for a clinically relevant depression diagnosis, 16.7% for an anxiety disorder and 13.9% for a PTSD diagnosis. At the second measurement point, it was 30.6% for depression, 15.7% for an anxiety disorder and 13.0% for PTSD. No significant changes between the measurement points were found for any of the disorders. In multiple linear regression analyses, higher perceived discrimination, a higher number of traumatic experiences and a shorter duration of residence permission were shown to be the most important pre- and post-migration predictors of psychological stress independent of the time of measurement. Conclusions: There is strong empirical evidence that the prevalence rates of mental distress among refugees are significantly higher compared to the overall population. However, it has not yet become clear how these prevalence rates change with an increasing length of stay in the host countries. The results of our study indicate that the psychological burden on this refugee population remains consistently high over time, despite partly improved living conditions, and confirm the importance of therapeutic interventions.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Depression; Follow-up; Generalized anxiety disorder; Germany; Mental distress; Mental health; Post-traumatic stress disorder; Register-based; Syrian refugees